TRANSFORMATIVE LEADERSHIP IN IMPROVING QUALITY IN ISLAMIC EDUCATION INSTITUTIONS - Tiarani Mirela tia; Amirrudin Amir; Hendri Rahmadani Hendri (Fakultas Agama Islam Universitas Wiralodra, 2022)
Leadership style is something that is used by a leader in running the wheels of the organization in an institution or agency, so that the leadership pattern used by a leader has a very large influence on the success or failure of the leadership wheel he is running. The existence of transformative leadership in an educational institution will help the educational institution to be more advanced and develop, with the role of the principal who will motivate its members and carry out the leadership wheel well too. This research is a qualitative type with the collection of data used in this study using library research techniques from various sources such as books, journal articles, the internet and so on. Based on the results of the research, the principal is obliged to make continuous quality improvements and use creativity so that he is able to carry out all educational activities even though they are still within limitations. (1) Idealized influence attitude (or charismatic influence) with wise principals in making decisions (2) Inspirational Motivation attitude with (3) Intellectual Stimulation attitude with new innovations (4) Individualized Consideration in improving the quality of Education. With the application of good transformational leadership in an Islamic educational institution will improve the quality of education in the institution as well.